2022
DOI: 10.12659/msm.938798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout in Healthcare Specialties: A Systematic Review Using Copenhagen and Maslach Burnout Inventories

Abstract: Background:This systematic review used the Copenhagen (CBI) and the Maslach (MBI) Burnout Inventories and its scales to assess and compare studies that involved students and workers in all medical specialties. Material/Methods: PubMed, ScienceDirect, Scopus, Wiley Library, and Web of Science databases were searched using keywords and Medical Subject Headings. Identified studies were in English, published between 2008 and 2022, measured the burnout of healthcare workers and students by using CBI and MBI, and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…Approximately one out of four (24.52 %) medical employees were burnt out across all the aforementioned aspects of the MBI. However, statistics were not as severe as in some other parts of the world, as some studies have shown, that over two-thirds of doctors faced severe overall burnout (Alahmari, 2022). There were no statistically significant differences between men and women in terms of burnout.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Approximately one out of four (24.52 %) medical employees were burnt out across all the aforementioned aspects of the MBI. However, statistics were not as severe as in some other parts of the world, as some studies have shown, that over two-thirds of doctors faced severe overall burnout (Alahmari, 2022). There were no statistically significant differences between men and women in terms of burnout.…”
Section: Discussionmentioning
confidence: 63%
“…It indicated that emotional exhaustion and depersonalisation had a statistically significant negative impact on students' health (Nteveros, et al, 2020). Most previous studies have not included both the CBI and MBI scales, with only 11 publications of this kind found in databases (Alahmari, 2022). All the previous studies were meta-analyses (Shoman, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the reduction in workload and stress caused by the temporary reduction of clinical rotations by the university [ 31 , 32 ]. More importantly, previous studies show that the Copenhagen Burnout Inventory tends to show relatively higher rates of burnout compared to the MBI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11] Recently, a review published by Alahmari et al, 2022, stated that Copenhagen Burnout Questionnaire is usually used for the measurement of burnout among samples with the same category of speciality, as well as for small sample size studies. [12] The prevalence of burnout syndrome in dentists has been thoroughly studied. [13] A recent systematic review found that dentists face a higher level of burnout compared to students from other professions.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%